Case report: Infection-associated HPS during pregnancy cured by HLH-94 protocol with induction therapy of ruxolitinib - Cen, Tianqi; Xuan, Weixia; Huang, Shaohui; Wang, Ziqi; Shen, Lijun; Zhang, Moyuan; Fang, Jinzhou; Yang, Shenying; Zhang, Xiaoju (Frontiers in Immunology, 2024)
Hemophagocytic syndrome (HPS) is a rapidly progressive and highly fatal disease, and is even more complex when it occurs during pregnancy. Currently, the HLH-94 protocol is commonly used for treatment for HPS, with ruxolitinib being mostly used for salvage therapy. Here, we report a pregnant woman who presented with fever, thrombocytopenia, splenomegaly, and subsequently developed into severe pneumonia and multiple organ dysfunction(MODS). The patient was diagnosed as HPS based on clinical manifestations, laboratory indexes, and hemophagocytosis observed in bone marrow aspirate smear. After receiving ruxolitinib as induction therapy combined with HLH-94 protocol, the patient significantly improved and eventually cured.